2022
DOI: 10.1007/s11104-022-05703-y
|View full text |Cite
|
Sign up to set email alerts
|

Response of a grassland species to dry environmental conditions from water stable isotopic monitoring: no evident shift in root water uptake to wetter soil layers

Abstract: Aims We aimed at assessing the influence of above- and below-ground environmental conditions over the performance of Centaurea jacea L., a drought-resistant grassland forb species. Methods Transpiration rate, CO2 assimilation rate, leaf water potential, instantaneous and intrinsic water use efficiency, temperature, relative humidity, vapor pressure deficit and soil water content in one plant and root length density in four plants, all grown in custom-made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The high deep-water uptake percentages observed in the B2WALD drought demonstrate that RWU from overlying soil was strongly limited, even though unbound water (Ψ soil > −1.5 MPa) was still available in the middle soil compartment. This could indicate that few fine roots were present therein and/or the measured trees developed higher root length densities above the impermeable concrete floor as observed in a column experiment ( Deseano Diaz et al, 2022 ). This deep root growth might be a response to the current or previous droughts ( Fan et al, 2017 ), and could be the reason for the observed mid-drought decrease in deep-water, thus indicating the below-ground drought adaptability of trees in the humid tropics.…”
Section: Discussionmentioning
confidence: 64%
“…The high deep-water uptake percentages observed in the B2WALD drought demonstrate that RWU from overlying soil was strongly limited, even though unbound water (Ψ soil > −1.5 MPa) was still available in the middle soil compartment. This could indicate that few fine roots were present therein and/or the measured trees developed higher root length densities above the impermeable concrete floor as observed in a column experiment ( Deseano Diaz et al, 2022 ). This deep root growth might be a response to the current or previous droughts ( Fan et al, 2017 ), and could be the reason for the observed mid-drought decrease in deep-water, thus indicating the below-ground drought adaptability of trees in the humid tropics.…”
Section: Discussionmentioning
confidence: 64%
“…We find that vegetation preferentially utilizes the water from shallow soil in semi-arid regions and in regions with low tree cover, which is related to the continuous availability of near-surface water and a lack of deep rooting systems, respectively. The stronger correlation of NIRv with SSM than with TWS is supported by sitelevel studies that find higher root water uptake of surface soil moisture (Brinkmann et al, 2019;Gessler et al, 2022;Deseano Diaz et al, 2023;Kulmatiski and Beard, 2013) when deeper water is also available. Some local studies however find a higher root water uptake from deeper layers (Zhu et al, 2023).…”
Section: Discussionmentioning
confidence: 88%
“…This means that the uptake of deeper soil layers cannot compensate for the loss of water uptake from the dry topsoil. Contrary to trees, grasses do not shift their uptake depth (Deseano Diaz et al, 2023) or even extract water from the most shallow soils (Prechsl et al, 2015;Kulmatiski and Beard, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(Deseano Diaz et al, 2022a;Volkmann et al, 2016b;Volkmann and Weiler, 2014) and higher temporal resolution (daily to sub daily scale e.g., Mennekes et al, 2021;Kübert et al, 2020;Piayda et al, 2017;Volkmann et al, 2016b) for relatively low monitoring costs with high accuracy (Volkmann and Weiler, 2014). Beyer et al (2020) provided a broad review of insitu measuring methods for water stable isotopes.…”
Section: New Methodological Perspectivesmentioning
confidence: 99%
“…However, isotopic nonsteady state conditions were encountered that limited measurements in the morning and evening. Indeed, the prevalence of isotopic non-steady state during most parts of the day (Dubbert et al, 2017(Dubbert et al, , 2014Kübert et al, 2022) has been a hindrance to utilize chamber measurements coupled to laser spectrometers in the field to infer xylem isotopic composition in high temporal resolution (Deseano Diaz et al, 2022a;Kühnhammer et al, 2020). Nevertheless, a recent study clearly demonstrated that integrated to daily resolution, in-situ chamber measurements of transpiration are very well suited to reflect steady state and hence dynamics in the xylem isotopic composition of both woody and non-woody species (Kübert et al, 2022).…”
Section: Volkmann Et Al (2016b) For Example Applied a Closed Chamber ...mentioning
confidence: 99%